Design and optimization of a powered ankle-foot prosthesis using a geared five-bar spring mechanism. (4th May 2017) - Dong, Dianbiao; Ge, Wenjie; Liu, Shumin; Xia, Fan; Sun, Yuanxi
To replace the lost limb, the active prosthesis foot has been investigated for several decades. The current powered ankle-foot prostheses function like a human ankle using accurate control systems. However, it is still hard to accurately mimic the impedance characteristics of the human ankle, especially at the end of the controlled dorsiflexion phase. This article presents the mechanical design, optimization, and experiment evaluation of a novel powered ankle-foot prosthesis using a geared five-bar spring mechanism. Compared with the traditional structure of single axis with elastic unit, the geared five-bar spring mechanism has more flexible movements. The optimization and experiment results of the geared five-bar spring mechanism show that it can provide a better performance on impedance torque in controlled dorsiflexion phase. Compared with the traditional powered ankle-foot prosthesis, the powered ankle-foot prosthesis using the geared five-bar spring mechanism may have the ability to provide the patients with better security during controlled dorsiflexion phase.